First environmental isolation of Cryptococcus gattii, genotype AFLP5, from India and a global review. Issue 3 (22nd January 2013) - Chowdhary, A.; Prakash, A.; Randhawa, H. S.; Kathuria, S.; Hagen, F.; Klaassen, C. H.; Meis, J. F.
Summary We report the first environmental isolation from India of Cryptococcus gattii, genotype amplified fragment length polymorphism 5 (AFLP5), which is one of the rarely reported genotypes of this pathogen. It originated from decayed wood inside a trunk hollow of Manilkara hexandra, a native tree in Delhi. We investigated 101 isolates of C. gattii, originating from 556 samples of decayed wood inside trunk hollows of 311 heterogeneous tree species and their surrounding soil. Of these, only a solitary isolate proved to be AFLP5, the remainder belonged to AFLP4. Antifungal susceptibility testing showed a low MIC90 (0.25 μg ml−1) of the new azoles posaconazole and isavuconazole for these environmental isolates. Genotype AFLP5 has been mainly reported from environmental sources in Colombia and from clinical sources in California (USA), where it seems to be endemic. Phylogenetic analysis of multi‐locus sequence typing data showed that the Indian AFLP5 C. gattii isolate had a distinct profile compared with a cluster of mainly Colombian and Californian C. gattii AFLP5 isolates. As molecular typing of human pathogenic fungi is still in its infancy and not accessible to many countries, our current knowledge cannot be taken as reflective of the true geographic distribution of C. gattii AFLP5 or its other rarely reported molecular types.